2010
DOI: 10.3174/ajnr.a2233
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Dynamic Radiographs in Diagnosing Painful Vertebrae in Osteoporotic Compression Fractures

Abstract: BACKGROUND AND PURPOSE:Many authors have reported the increase in vertebral body height after vertebroplasty; if the fractured vertebrae are mobile, we should be able to demonstrate their mobility in radiographs. The purpose of this study was to discover the diagnostic value of dynamic radiographs and the percentage of mobile vertebrae in painful VCFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 7 publications
3
26
0
1
Order By: Relevance
“…They concluded that in any article in which vertebral height restoration is claimed, there must be control for the occurrence of dynamic mobility of the fractured vertebrae. In a study by Chen et al, 7 87.5% of 144 MR imagingϪproved edematous VCFs were demonstrated to be mobile. The average vertebral body height increase from sitting to supine with bolster lateral radiographs was 8.48 Ϯ 5.36 mm (range, Ϫ1.17-24.04 mm), which was statistically significant (P Ͻ .001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that in any article in which vertebral height restoration is claimed, there must be control for the occurrence of dynamic mobility of the fractured vertebrae. In a study by Chen et al, 7 87.5% of 144 MR imagingϪproved edematous VCFs were demonstrated to be mobile. The average vertebral body height increase from sitting to supine with bolster lateral radiographs was 8.48 Ϯ 5.36 mm (range, Ϫ1.17-24.04 mm), which was statistically significant (P Ͻ .001).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study, which used sitting and supine cross-table (with a bolster beneath) lateral radiographs, demonstrated that dynamic mobility occurred in 87.5% of the treated vertebrae. 7 The authors found that 87.5% of 144 MR imagingϪproved edematous VCFs were demonstrated to be mobile. The average vertebral body height increase from sitting position to supine with bolster was 8.48 Ϯ 5.36 mm.…”
mentioning
confidence: 99%
“…Dynamic fracture mobility raises concern in OVCFs as it implies complete corticocancellous disruption and permits the vertebral height restoration after postural reduction3,17). As the injury of OVCFs produced is an anterior wedge fracture, postural reduction in prone hyperextended position can re-expand the compressed anterior column11).…”
Section: Discussionmentioning
confidence: 99%
“…There is a reduction of post-fracture kyphosis in up to 47% to 92% cases after kyphoplasty4,7,15,18). However, it has been demonstrated that many OVCFs are mobile and postural reduction can lead to clinically significant height restoration3,17). Therefore, the real efficacy of the kyphoplasty procedure can only be evaluated after the postural reduction in prone hyperextended position3,11,23).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, McKiernan et al4) suggested the usefulness of supine cross-table lateral radiographs (SuLRs) and recommended examination for evaluating dynamic mobility. Several authors followed these methods and confirmed its usefulness 5,6). However, there are several problems in the methods including possible pain stimulations and different positions with real operative settings.…”
mentioning
confidence: 96%